Volumetric properties and leaching effect of asphalt mixes with electric arc furnace steel slag and copper mine tailings - Oluwasola, Ebenezer Akin; Mohd Rosli Hainin; Md. Maniruzzaman A. Aziz; M. Naqiuddin M. Warid (Universiti Kebangsaan Malaysia, 2016)
This study focuses on the potential of electric arc furnace (EAF) steel slag and copper mine tailings as asphalt paving materials with respect to issues of volumetric properties and leaching. In this study, four different asphalt mixes were investigated; each contained EAF steel slag and copper mine tailings of various proportions. Apart from the microstructure analysis of the materials, a toxicity characteristics leaching procedure (TCLP) test was conducted on both the mixes and the aggregates. All the mixes were evaluated by the following parameters: Voids in the mineral aggregates (VMA), voids in total mix (VTM), voids filled with asphalt (VFA), Marshall stability and flow and specific gravity. F-test ANNOVA was used to evaluate the degree of significance of the mixes with each of the evaluated standards. It was observed that the mixes containing either EAF steel slag or copper mine tailings or both gave better results than the control mix. In terms of the TCLP test, none of the detected hazardous elements exceeded the standard limits, which indicates the possibility of using them as construction materials.